PENERAPAN SAK-ETAP PADA ENTITAS KOPERASI (Studi Kasus Pada KUD Tri Karsa Jaya Kec. Bangsalsari Kab. Jember) - Yulinartati Yulinartati (Jurnal Ekonomi Akuntansi dan Manajemen, 2013)
Financial reportis a report that shows the financial position consisting of revenues, expenses, assets, capital, and debt in a given period as a result of the transactions. Th financial statements should reflect the purpose cooperative of cooperatives, the balance of the calculation must be clearly informed cooperative activities with its members, because it is the income of members is presented separately f rom income derived from non - member transactions. Presentation was more reflective of that cooperative effort is more concerned with the transaction or service to the members of the non -members. Financial statements are the KUD "Tri Karsa Jaya" consisting of the balance sheet and the balance of the report. At the balance sheet of financial statements provide information about the assets, liabilities, and equity. Presentation of financial statements KUD " Tri Karsa Jaya" is not in accordance with GAAP on the accounting co-ETAP, because KUD "Tri Karsa Jaya" has not made ​​ a cash flow statement, statement of changes in equity, and notes to the financial statements. Keywords: Financial Statements, Income Statements, Cooperative